A practical drug discovery project at the undergraduate level - Fray, Michael J.; Macdonald, Simon J.F.; Baldwin, Ian R.; Barton, Nick; Brown, Jack; Campbell, Ian B.; Churcher, Ian; Coe, Diane M.; Cooper, Anthony W.J.; Craven, Andrew P.; Fisher, Gail; Inglis, Graham G.A.; et al. (Elsevier, 2013)
A practical drug discovery project for third-year undergraduates is described. No previous knowledge of medicinal chemistry is assumed. Initial lecture-workshops cover the basic principles; then students are asked to improve the profile of a weakly potent, poorly soluble PI3K inhibitor (1). Compound array design, molecular modelling and screening data analysis are followed by laboratory work in which each student, as part of a team, attempts to synthesise at least two target compounds. The project benefits from significant industrial support, including lectures, student mentoring and consumables. The aim is to make the learning experience as close as possible to real-life industrial situations. Forty-eight target compounds have been prepared, the best of which (5b, 5j, 6b and 6ap) improved the potency and aqueous solubility of the lead compound (1) by 100-1000 fold and 10-fold, respectively.